Step-by-step Solution

Solve the inequality $x\left(x-3\right)-5x\geq x^2+3x-6$

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Step-by-step explanation

Problem to solve:

$x\left(x-3\right)-5x\ge x^2+3x-6$

Learn how to solve inequalities problems step by step online.

$x\left(x-3\right)-5x-\left(x^2+3x\right)\geq -6$

Unlock this full step-by-step solution!

Learn how to solve inequalities problems step by step online. Solve the inequality x(x-3)-5x>=x^2+3x-6. Grouping terms. Solve the product x\left(x-3\right). Solve the product -\left(x^2+3x\right). Adding -3x and -3x.

Final Answer

$x\leq \frac{6}{11}$

Problem Analysis

$x\left(x-3\right)-5x\ge x^2+3x-6$

Main topic:

Inequalities

Time to solve it:

~ 0.05 seconds